Impact of Economic Growth, Inflation, Government Effectiveness, and Corruption Control on Gross Capital Formation of Nepal - Dahal, Arjun Kumar (Adhyayan Journal, 2025)
This study aims to investigate the impact of inflation rate, economic growth, effectiveness of government, and corruption control on gross capital formation in Nepal. Secondary data, which are collected from the World Bank Report and Nepal's economic surveys, is used in the study. The descriptive and correlational research designs are used to analyze the impact of predictor variables. This study is guided by positivist research philosophy and is mainly quantitative. To investigate the effects and validate the model, econometric tools include descriptive statistics, correlation analysis, dynamic ordinary least squares (DOLS), Phillips-Perron unit root test, and variance inflation factor. Other measures of residual testing include the Hansen parameter instability test, normality test, residual and standardized residual graph, and actual fitted residual graph. The effectiveness of government has a high degree (r=0.722) of positive association with gross capital formation. Economic growth, corruption control, the effectiveness of government, inflation rate, and gross capital formation have long-run co integration. Economic growth has a positive and significant impact on gross capital formation. One unit increase in economic growth results in a 1.4594 unit increase in gross capital formation in Nepal. The government's effectiveness also positively and significantly impacts gross capital formation in Nepal. One unit increase in the effectiveness of the government results from 0.8125 unit increase in capital formation in Nepal. The inflation rate has no significant impact on gross capital formation in Nepal. But surprisingly, corruption control negatively and significantly impacts capital formation. One unit change in corruption control resulted in a 0.8217 unit decrease in capital formation. About 97.57 percent variation in capital formation is determined by economic growth, effectiveness of government, corruption control, and inflation rate in Nepal. Policymakers should focus on enhancing economic growth through infrastructure, education, and business environment improvements, ensuring effective governance and stable inflation, and fine-tuning anti-corruption strategies to support capital formation in Nepal.